2022
DOI: 10.3390/toxins14100660
|View full text |Cite
|
Sign up to set email alerts
|

Indoxyl Sulfate Might Play a Role in Sarcopenia, While Myostatin Is an Indicator of Muscle Mass in Patients with Chronic Kidney Disease: Analysis from the RECOVERY Study

Abstract: Serum myostatin and indoxyl sulfate (IS) levels increase with kidney function decline and may function as uremic toxins in chronic kidney disease (CKD)-related sarcopenia. Herein, we analyzed the association between serum myostatin and IS levels and sarcopenia in patients with CKD, by performing a post hoc analysis of baseline data extracted from the RECOVERY study (clinicaltrials.gov: NCT03788252) of 150 patients with CKD. We stratified patients into two groups according to the median value of myostatin (cuto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Vanholder et al ranked IS toxicity with the second highest evidence score in SPBMs, such as inflammation, CVD, CKD–MBD, fibrosis metabolic function, and thrombogenicity [ 28 ]. IS acts widely across various organs, tissues, and cells such as bones [ 29 , 30 , 31 , 32 , 33 ], skeletal muscles [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ], and myocardium [ 45 , 46 , 47 , 48 , 49 , 50 , 51 ], causing dysfunction in their functions. A clinical study has shown that the serum levels of IS increased with CKD progression, and high levels of serum IS are independently associated with an increased all-cause mortality and cardiovascular mortality in CKD patients [ 25 ] and a trend towards increased cardiovascular events in hemodialysis patients [ 23 ].…”
Section: Uremic Toxins and Cardiovascular Disorders In Ckd Patientsmentioning
confidence: 99%
“…Vanholder et al ranked IS toxicity with the second highest evidence score in SPBMs, such as inflammation, CVD, CKD–MBD, fibrosis metabolic function, and thrombogenicity [ 28 ]. IS acts widely across various organs, tissues, and cells such as bones [ 29 , 30 , 31 , 32 , 33 ], skeletal muscles [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ], and myocardium [ 45 , 46 , 47 , 48 , 49 , 50 , 51 ], causing dysfunction in their functions. A clinical study has shown that the serum levels of IS increased with CKD progression, and high levels of serum IS are independently associated with an increased all-cause mortality and cardiovascular mortality in CKD patients [ 25 ] and a trend towards increased cardiovascular events in hemodialysis patients [ 23 ].…”
Section: Uremic Toxins and Cardiovascular Disorders In Ckd Patientsmentioning
confidence: 99%